Piezoelectric and Thermoelectric Properties of Transition Metal-Doped Compounds: An Ab-initio Study - MEZILET Oum Keltoum (Université de Mostaganem, 2025)
In this work, advanced ab initio DFT calculations using GGA-PBsol and nKTB-mBJ functionals within the full-potential linear augmented plane wave (FP-LAPW) method were employed to investigate key characteristics, such as the structural, electronic, elastic, piezoelectric, dielectric, thermodynamic, and thermoelectric properties of two eco-friendly materials: the perovskite Na₀.₅Bi₀.₅TiO₃ (NBT) and YxAl₁₋ₓN (with 0≤ x ≤ 0.375) to explore their potential for application in piezoelectric and thermoelectric technologies. The first part of the study focused on perovskite Na₀.₅Bi₀.₅TiO₃ (NBT), crystalized in rhombohedral (R3c), tetragonal (Pb4m), and cubic (Pm3̅m) phases. These crystals exhibited indirect bandgaps of 3.05–3.29 eV, elastic stability, and high piezoelectric coefficients in the tetragonal phase [d15 = 101.1 pC/N, d31 = -51.3 pC/N, and d33 = 81.1 pC/N]. The thermoelectric properties of NBT included Seebeck coefficients of up to 201.42 μV/K at 500 K and ZT values reaching 2.76 at 700 K. In the second part of the study, DFT simulations revealed a near-linear variation in lattice parameters with increasing yttrium content for YxAl₁₋ₓN (0≤ x ≤ 0.375) alloys, and tunable bandgaps ranging from 6.10 eV to 3.85 eV, making these alloys suitable for ultraviolet emission applications. Additionally, BoltzTraP calculations indicated promising electronic transport properties, including Seebeck coefficients up to 213.9 μV/K and a figure of merit (ZT) of ~0.72 at x = 0.25 (600 K). Thermal conductivity per relaxation time was also low, at κ/τ ~9.9 × 10¹³ W.m⁻¹.K⁻¹.s⁻¹. Piezoelectric coefficients for YxAl₁₋ₓN at x = 0.375 were significantly enhanced, with d33 = 17.5 pC/N, d15 = 11.07 pC/N, and d31 = 8.65 pC/N, representing increases of ~300%, ~400%, and ~370%, respectively, compared to pure AlN crystals. Finally, the results highlight the potential of Na₀.₅Bi₀.₅TiO₃ and YxAl₁₋ₓN for green energy applications, optoelectronics, high-performance piezoelectric devices, and high-power thermoelectric technologies.
Keywords: Ab initio DFT calculations; Piezoelectric performances; Thermoelectrics; Lead-free perovskite Na₀.₅Bi₀.₅TiO₃; YxAl₁₋ₓN alloys; Green energy and Microtechnology applications.